Taxithelium napalense acts against free radicals and diabetes mellitus - Vinay Bharadwaj Tatipamula; Kishore Naidu Killari; Alekhya Ketha; Vedula Girija Sastry (Bangladesh Pharmacological Society, 2017)
In this work, Taxithelium nepalense ethanolic extract and its fractions were evaluated for the antidiabetic activity in rat based on phytochemical and free radical scavenging properties. The ethanolic extract, fraction IV and V significantly attenuated the blood glucose levels at 600, 200 and 200 mg/kg with 50.0, 33.5 and 42.0% inhibition respectively. The histopathological studies were manifesting the recuperation of damaged cells in liver and pancreas tissues. The outcomes of the present work affirm that the T. nepalense has a potency to plummet the overproduction of free radicals and blood glucose levels in the diabetic-induced rat. Video Clip of Methodology: Induction of diabetes:  1 min 50 sec   Full Screen   Alternate